Object play in infants with autism spectrum disorder: A longitudinal retrospective video analysis. (June 2017) - Wilson, Kaitlyn P; Carter, Mary W; Wiener, Heather L; DeRamus, Margaret L; Bulluck, John C; Watson, Linda R; Crais, Elizabeth R; Baranek, Grace T
Background and aims: Early play behaviors may provide important information regarding later-diagnosed developmental delays. Play behaviors of young children with autism spectrum disorder are restricted in diversity, frequency, and complexity. Most autism spectrum disorder research focuses on play in children over 18 months of age. This study examined three groups of infants (later diagnosed with autism spectrum disorder, later diagnosed with other developmental disorders, and typically developing) with the aims of: (1) describing the play behaviors of the three groups of infants at two time points (9–12 months and 15–18 months); (2) examining group differences in four hierarchical levels of play at both time points; (3) comparing groups with respect to the highest level of play achieved; and (4) determining if the highest level of play achieved by infants with autism spectrum disorder and other developmental delays correlated with later developmental outcomes. Methods: The current study used longitudinal retrospective video analysis to examine object play behaviors of the three groups of infants (total n = 92) at two time points (time 1: 9–12 months of age, and time 2: 15–18 months of age). Coding of play behaviors was based on existing literature and distribution of data from the current study. Developmental outcomes examined were measured using the Vineland Adaptive Behavior Scales, Childhood Autism Rating Scale, and a non-verbal developmental quotient calculated using visual reception scores from the Mullen Scales for Early Learning . Results: Results indicate group differences in play, with infants later diagnosed with autism spectrum disorder showing significantly less sophisticated play than those with typical development. In addition, modest but significant correlations were found between highest level of play achieved at time 1 (9–12 months) and time 2 (15–18 months) and later outcomes for the autism spectrum disorder group. Conclusions and implications: Results suggest that examination of infant play behaviors is important for early screening and intervention planning to potentially mitigate effects on later developmental outcomes.